Behavioral activities of white-lipped peccary (Tayassu pecari, Link, 1795) in a semi-intensive farming system in Brazil - Oliveira, M. H. V. [UNESP]; Oliveira, J. M.; Domingues, D. H. B.; Hosken, F. M.; Taroco, G.; Gaya, L. G.; Ferreira, F. N. A.; Martins, E. H. [UNESP]; Malheiros, J. M.; Correia, L. E. C. S. [UNESP]; Vilar, C. S. M. M.; Reis, R. S. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2020)
This study aimed to describe the main behaviors of white-lipped peccaries (Tayassu pecari) expressed in a semi intensive production system in Brazil. The behavioral activities of two groups of peccaries allocated in two paddocks were assessed, totaling 17 adult animals and eventual pups in different developmental stages. The animals were visually observed using the ad libitum sampling and scan sample methods during the adaptation and experimental phases, respectively. The animals were evaluated in the morning, afternoon, and at night. The behavioral activities observed by ad libitum sampling comprised feeding, pool contact, moving, staying inside the handling area, resting, mud bathing, mutual rubbing, rubbing, aggression, sexual behavior, copulation, foraging, breastfeeding, sleeping, territorial marking, interactions, birthing, gnawing, and other behaviors. All behaviors observed by the ad libitum sampling method were confirmed in the experimental period by scan sample, except for territorial marking and birthing. The effects of time of day were statistically significant (p <0.05) for eating, pool contact, movement, staying inside the handling area, resting, mud bathing and sleeping. These results contribute to the understanding of instinctive animal habits and to the development of nutritional, environmental and health management protocols that meet the requirements of peccaries.
Keywords: animal welfare; animal production; conservation; ethology; wildlife